Small GTPases in peroxisome dynamics - Just, Wilhelm W.; Peränen, Johan (Biochimica et biophysica acta, 2016)
In this review article, we summarize current knowledge on peroxisome biogenesis/functions and the role that small GTPases may play in these processes. Precise intracellular distribution of cell organelles requires their regulated association to microtubules and the actin cytoskeleton. In this respect, RhoGDP/RhoGTP favor binding of peroxisomes to microtubules and actin filaments. In its GTP-bound form, RhoA activates a regulatory cascade involving Rho kinaseII and non-muscle myosinIIA. Such interactions frequently depend on phosphoinositides (PIs) of which PI4P, PI(4,5)P2, and PI(3,5)P2 were found to be present in the peroxisomal membrane. PIs are pivotal determinants of intracellular signaling and known to regulate a wide range of cellular functions. In many of these functions, small GTPases are implicated. The small GTPase ADP-ribosylation factor 1 (Arf1), for example, is known to stimulate synthesis of PI4P and PI(4,5)P2 on the Golgi to regulate protein and lipid sorting. In vitro binding assays localized Arf1 and the COPI complex to peroxisomes. In light of the recent discussion of pre-peroxisomal vesicle generation at the ER, peroxisomal Arf1-COPI vesicles may serve retrograde transport of ER-resident components. A mass spectrometric screen localized various Rab proteins to peroxisomes. Overexpression of these proteins in combination with laser-scanning fluorescence microscopy co-localized Rab6, Rab8, Rab10, Rab14, and Rab18 with peroxisomal structures. By analogy to the role these proteins play in other organelle dynamics, we may envisage what the function of these proteins may be in relation to the peroxisomal compartment. This article is part of a Special Issue entitled: Peroxisomes edited by Ralf Erdmann.
Gesehen am 06.05.2020